Facilitators and Barriers to Antiretroviral Therapy Adherence among Ghanaian Patients: A Multi-Case Study - Yarney, L.; Amankwaah, A.K.; Mba, C.J.; Asamoah, K.; Bawole, J.N. (Stellenbosch University Library and Information Service, 2016)
The only remedy to manage AIDS remains ART, making adherence to ART paramount in AIDS management. Non-adherence can impede the sustainability of programmes intended at successful HIV and AIDS care. We studied individual, social and service delivery factors influencing adherence to ART. Mixed method involving 133 participants was used, data were analysed using SPSS version 18.0. There were statistically significant relationship between availability of drugs, privacy, relations with health professionals, counselling services, and adherence to ART ((p = 0.008, p = 0.001, p = 0.008 and p = 0.018 respectively). Although age, gender, and perceived efficacy and need for ART were not significantly related to adherence (p > .05 in all cases), the qualitative findings indicated otherwise. For AIDS patients, ART is tantamount to life, thus, stakeholders should place priority on availability of ARVs and well trained personnel to deliver efficient and quality services to allay the fears of patients.
Keywords: Facilitators; Barriers; ART Adherence; Ghana